The analgesic and anti-inflammatory effects of subcutaneous bupivacaine, morphine and tramadol in rats - (:unkn) unknown (My University, 2004)
The analgesic and anti-inflammatory effects of subcutaneously administered bupivacaine, morphine and tramadol on formalin-induced inflammation were compared. 0.25 % bupivacaine in Group B, 20 mg/kg tramadol in Group T, 1 mg/kg morphine in Group M and 0.9 % NaCl in Group S in a volume of 200 micro l were injected into the right hind paw of the rats (n: 40) 15 minutes before injection of 50 micro l 5 % formalin. Sedation and pain behaviour scores, number of flinches and licking-time were recorded. The degree of dermal edema, intraneural edema, vasodilation, erythrodiapedesis, infiltration of polymorphonuclear leukocyte/lymphocyte and mast cell counts were analyzed histopathologically. In Group T and B, circumferential changes were lower than in Group M and S. The pain behaviour scores were significantly lower in Group T and B. The number of flinches in Group T was lower than Group B and S. The vasodilation was significant only in Group M. The dermal edema was limited to deep dermis only in Group T. Preinflammational subcutaneous tramadol infiltration can provide effective analgesia and may have anti-inflammatory effects.
Keywords: Animals; Male; Rats; Formaldehyde; Random Allocation; Inflammation; Pain; Pain Measurement; Rats, Sprague-Dawley; Injections, Subcutaneous; Morphine; Anesthetics, Local; Analgesics, Opioid; Tramadol; Bupivacaine